P11.54.A Factors effecting early diagnosis in neurolymphomatosis. (5th September 2022) - Egert, A; Karschnia, P; Huttner, A; Baehring, J M; Kaulen, L D
Abstract: Background: Neurolymphomatosis is defined as infiltration of the peripheral nervous system by non-Hodgkin lymphoma (NHL). Given its rarity, correct diagnosis is often delayed. Here we assessed diagnostic work-up and factors affecting timely diagnosis at a tertiary referral center. Material and Methods: The quality control database of the Section of Neuro-Oncology at Yale Cancer Center was searched for neurolymphomatosis cases seen between 2000 and 2021. Clinical, radiological and pathological findings were collected. Factors affecting the interval from symptom onset to diagnosis were investigated in univariate analysis using SPSS version 27. P-values <0.05 were considered statistically significant. Results: We identified 22 cases of neurolymphomatosis (primary n=7, secondary n=15) with secondary disease diagnosed a median of 16 months (range: 4-144) after NHL. Patients presented with painful polyneuropathy (n=16), painless polyneuropathy (n=4), cranial neuropathy (n=3), and autonomic neuropathy (n=1). Diagnosis was nerve biopsy-based (n=11) or resulted from integration of imaging findings (n=11) with NHL history (n=5) or detection of NHL in the cerebrospinal fluid (n=6), respectively. Lesions localized to nerve roots (n=16), peripheral nerves (n=12), plexus (n=10), cranial (n=3) or autonomic (n=1) nerves. Histologically, most cases were classified as diffuse-large B-cell lymphoma (n=18). Median interval from symptom onset to diagnosis was 3 months (range: 1-12). Secondary neurolymphomatosis (p=0.02) and FDG-PET imaging (p<0.01) were associated with an earlier diagnosis. Conclusion: Diagnosis of neurolymphomatosis requires a high degree of clinical suspicion with subsequent integration of clinical, radiological and pathological findings. FDG-PET, the imaging gold standard, and a known NHL history correlated with an earlier diagnosis.